1984
DOI: 10.1042/bj2190857
|View full text |Cite
|
Sign up to set email alerts
|

Glycosidases induced in Aspergillus tamarii. Secreted α-d-galactosidase and β-d-mannanase

Abstract: An alpha-D-galactosidase (EC 3.2.1.22) and a beta-D-mannanase (EC 3.2.1.78), which were secreted into the growth medium when Aspergillus tamarii was cultivated in the presence of galactomannan, were purified by a procedure including chromatography on hydroxyapatite and DEAE-cellulose columns. Each of these enzymes showed a single protein band, corresponding to their respective activities, on polyacrylamide-gel electrophoresis. Both enzymes were shown to be glycoproteins containing N-acetylglucosamine, mannose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…The presence of galactose residues on the mannan backbone significantly hinders the activity of ␤-mannanase (252), but this effect is small if the galactose residues in the vicinity of the cleavage point are all on the same side of the main chain (251). ␤-Mannanases release predominantly mannobiose and mannotriose from mannan, confirming that they are true endohydrolases (4,64,105,306). It has been shown that A. niger ␤-mannanase binds to four mannose residues during catalysis (249).…”
Section: Degradation Of the Galacto(gluco)mannan Backbonementioning
confidence: 70%
See 2 more Smart Citations
“…The presence of galactose residues on the mannan backbone significantly hinders the activity of ␤-mannanase (252), but this effect is small if the galactose residues in the vicinity of the cleavage point are all on the same side of the main chain (251). ␤-Mannanases release predominantly mannobiose and mannotriose from mannan, confirming that they are true endohydrolases (4,64,105,306). It has been shown that A. niger ␤-mannanase binds to four mannose residues during catalysis (249).…”
Section: Degradation Of the Galacto(gluco)mannan Backbonementioning
confidence: 70%
“…The ability of ␤-mannanases to degrade the mannan backbone depends on several factors, such as the number and distribution of the substituents on the backbone and the ratio of glucose to mannose (250). ␤-Mannanase is most active on galactomannans with a low substitution of the backbone (64). The presence of galactose residues on the mannan backbone significantly hinders the activity of ␤-mannanase (252), but this effect is small if the galactose residues in the vicinity of the cleavage point are all on the same side of the main chain (251).…”
Section: Degradation Of the Galacto(gluco)mannan Backbonementioning
confidence: 99%
See 1 more Smart Citation
“…Two of these, galactosidases I and I1 isolated from mycelial extracts, are highly active on melibiose but do not attack galactomannan (Civas et al, 19844. The third enzyme, galactosidase 111 isolated from the culture medium, is only slightly active towards melibiose but is able to liberate galactose from manno-oligosaccharides and from polymeric galactomannan (Civas et al, 1984b).…”
Section: Discussionmentioning
confidence: 99%
“…The capability of some a-galactosidases to release a-galactosyl side groups from galactomannans has also been studied. Enzymes that can act on intact polymeric galactomannan have been isolated from seeds of Cyumopsis tetragonoloba (guar; Bulpin et al, 1990), Phaseolus vulgaris (French bean; Dhar et al, 1994) and Vigna rudiuta (mung bean; Dey, 1984) and from filamentous fungi such as Aspergillus tamarii (Civas et al, 1984b), Aspergillus niger (Adya and Elbein, 1977;Kaneko et al, 1991) and Trichoderma reesei (Zeilinger et al, 1993). Some cx-galactosidases have no activity on galactomannan such as the one described for Mortierella vinacea (Kaneko et al, 1990).…”
mentioning
confidence: 99%